Dynamical Analysis Applied to Passive Control of Vibrations in a Structural Model Incorporating SMA-SE Coil Springs. (10th July 2018) - Moraes, Yuri J. O.; Silva, Antonio A.; Rodrigues, Marcelo C.; de Lima, Antonio G. B.; dos Reis, Rômulo P. B.; da Silva, Paulo C. S.
Abstract : Mechanical vibrations are severe phenomena of the physical world. These oscillations may become undesirable and may cause temporary and even irreversible damage to the system. There are several techniques to minimizing these vibration effects ranging from passive methods to the use of controllers with smart materials. In this sense, this study aims to analyze a passive vibration control system installed in a structure that simulates two-floor buildings. This system based on the incorporation of one SMA-SE ( Superelastic Shape Memory Alloys ) coil springs configuration for energy dissipation and the addition of damping. Modal analysis was performed using analytical, numerical, and experimental methods. In an experimental basis, response amplitudes were analyzed for free and forced vibrations in different configurations. As compared with the structure configuration with steel spring, the forced vibrations FRF ( Frequency Response Function ) analysis showed a reduction in displacement transmissibility of up to 51% for the first modal shape and 73% for the second mode in the SMA-SE coil spring configuration. As for damping, there was a considerable increase in the order of 59% in the first mode and 119% in the second, for the SMA-SE springs configuration.